Laboratory study on recycling of sediments in paving blocks. Issue 6 (1st June 2015) - Missaoui, Amel; Said, Imen; Lafhaj, Zoubeir; Daoued, Samar; Ali, Imen Bel Hadj
Abstract : The aim of this paper is to study the feasibility, in a laboratory experiment, of using dredged marine sediments as substituents of sand in paving blocks. Marine sediments recycled in this study are dredged from Rades harbour, which is considered as one of the most important harbours in Tunisia. This study reports a problem related to the large tonnage of marine sediments, which are considered as wastes. To optimise the circular economy, the recycling of these wastes in construction materials seems to present an interesting solution. This paper is composed of three main parts. The first part deals with the physical, chemical and environmental characterisation of marine sediments. The second part includes a research study on an optimal formulation of the use of marine sediments in paving blocks. In this article, we present the six formulations studied. Over 80 blocks were produced at laboratory scale. The last part is devoted to the analysis of normative test results conducted on specimens. It reveals that the substitution of 12·5% of sands by marine sediments provides paving blocks comparable to standard ones.